Triangular cross-section peristaltic conveyor for transporting powders at high speed in printers. (18th June 2018) - Yamada, Yasuyuki; Ashigaki, Kyota; Yoshihama, Shun; Negishi, Kai; Kato, Koichi; Nakamura, Taro
ABSTRACT: Powder-based materials are widely used in various applications such as printing. In printing, low shear force and high-speed conveyance at low temperatures are required to prevent creating defects in materials. In a previous study, we developed a transportation device based on the human intestinal tract that successfully transported highly viscous and solid–liquid fluid mixes and powder material. In this study, we developed a tubular peristaltic conveyor capable of transporting powdered materials in a printer under the aforementioned conditions. The conveyor had a triangular cross-sectional area and a small air chamber to facilitate high-speed peristaltic motion. The performance of the conveyor was confirmed experimentally, and we achieved a conveyance rate of 81.5 g/s. GRAPHICAL ABSTRACT: